let $X=\{a_i\mid i\in I\}$ be a set , then the free abelian group on X is (isomorphic to) the group defined by the generators X and the relations (in multiplicative notation) $\{a_ia_ja_i^{-1}a_j^{-1}=e\mid i,j\in I\}$

here is where i need help..

let the free group on X be F , let N be the normal subgroup of F that is generated by the relations set Y , so i need to prove $G=F/N$ is abelian group and it has a nonempty basis . to prove the first one is easy , i am stuck on how to prove $F/N$ has a nonempty basis because i don't know what the element in group N general is

  • 4
    $\begingroup$ What is your question? $\endgroup$ – Tobias Kildetoft Dec 5 '14 at 14:19
  • $\begingroup$ prove this fact :) $\endgroup$ – Idele Dec 5 '14 at 14:20
  • $\begingroup$ So what did you try? Please show your work and tell us where you got stuck. $\endgroup$ – Harald Hanche-Olsen Dec 5 '14 at 14:22
  • $\begingroup$ And what definition of the free abelian group are you using? $\endgroup$ – Tobias Kildetoft Dec 5 '14 at 14:22
  • 2
    $\begingroup$ Have you tried to define a map in one direction or the other? There are not that many logical choices. $\endgroup$ – Tobias Kildetoft Dec 5 '14 at 14:33

From my point of view this is trivial but I could be missing something important from the OP's view.

First, $\;F/N\;$ abelian as clearly $\;F'\le N\;$ by definition of $\;N\;$ . About the non-empty set of generators the reason why I think this is trivial is that if $\;F=\langle\;f_i\;:\;i\in J\;\rangle\;$, then

$$\langle\;f_iN\;:\;i\in J\;\rangle=F/N$$

The only way the above can be empty is if $\;J=\emptyset\iff F=\{1\}\;$ , but for this trivial case...

Also, even if $\;F\;$ is abelian the above cannot be empty, but also this case can be considered trivial and we can, probably, assume $\;|J|\ge 2\;$

  • $\begingroup$ sorry i didn't make it clear . an abelian group G's nonempty basis X is a nonempty set that satisfy: <X>=G , and if $n_1x_1+n_2x_2+\cdots+n_rx_r=0$ then $n_1=n_2=\cdots=n_r=0$,where $x_k\in X,k=1,2,\cdots,r,n_k \in Z$ $\endgroup$ – Idele Dec 6 '14 at 15:52
  • $\begingroup$ @hctb, that's exactly what we have here in my answer. $\endgroup$ – Timbuc Dec 6 '14 at 18:45
  • $\begingroup$ but how to prove if $k_1,k_2,\cdots,k_r\in J,n_k\in Z$ and $f_{k_1}^{n_1}f_{k_2}^{n_2}\cdots f_{k_r}^{n_r}N=N$ which is $f_{k_1}^{n_1}f_{k_2}^{n_2}\cdots f_{k_r}^{n_r}\in N$ then $n_1=n_2=\cdots=n_r=0$ $\endgroup$ – Idele Dec 7 '14 at 2:24
  • 1
    $\begingroup$ @hctb Using for example the canonical normal form for an element in a free group. Try to prove the following very nice, and for me once surprising, theorem: if $\;F:=F(a_1,...,a_m)\;$ is the free group on $\;\{a_1,...,a_m\}\;$ and $\;w:=w(a_1,...,a_m)\;$ is a word in these letters, then the exponent sum $\;e_i\;$ of a letter $\;a_i\;$ is the sum of all the exponents to which the letter $\;a_i\;$ is raised in the word. For example, $\;e_2(a_1^2a_5a_6a_2^{-4}a_3a_2^2)=-2\;$ . The theorem is: a letter $\;w\;$ belongs to $\;F':=[F:F]\;$ iff $\;e_i=0\;$ for all $\;i\;$ . $\endgroup$ – Timbuc Dec 7 '14 at 3:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.